Recent Development in Pulmonary Valve Replacement after Tetralogy of Fallot Repair: The Emergence of Hybrid Approaches - Suleiman, Tariq; Kavinsky, Clifford J.; Skerritt, Clare; Kenny, Damien; Ilbawi, Michael N.; Caputo, Massimo (Frontiers in Surgery, 2015)
An increasing number of patients with tetralogy of Fallot require repeat surgical intervention for pulmonary valve replacement secondary to pulmonary regurgitation. Catheter-based interventions have emerged as an attractive alternative to surgery in this patient population but it is limited by patient size or the anatomy of the right ventricular outflow tract. Hybrid approaches involving both cardiac interventionists and surgeons are being developed to overcome these limitations. The purpose of this review is to highlight the recent advances in the hybrid field of pulmonary valve replacement, summarizing the advantages and disadvantages of the “traditional” surgical and the new catheter-based techniques and discuss the direction future research should take to determine the optimal management for individual patients.